ORGANIZATIONAL AND ECONOMIC MECHANISMS FOR CREATING NEW JOBS - Abdullayeva Nigora Shamsiddinovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Ensuring sustainable employment is a key priority for economic development and social well-being. In the face of rapid technological transformation and structural changes in the global economy, the need for effective organizational and economic mechanisms to support job creation has become increasingly urgent. This article analyzes the essential components of such mechanisms, including institutional reforms, financial incentives, and strategic partnerships between the public and private sectors. The study highlights best practices and provides policy recommendations aimed at improving labor market performance and stimulating inclusive growth.